Life cycle assessment of a microbial desalination cell for sustainable wastewater treatment and saline water desalination. (1st November 2018) - Zhang, Jingyi; Yuan, Heyang; Deng, Yelin; Zha, Yuanchun; Abu-Reesh, Ibrahim M.; He, Zhen; Yuan, Chris
Abstract: Microbial desalination cells (MDCs), with bifunctional capacity to simultaneously treat wastewater and desalinate seawater at low energy consumption, have attracted great attention in recent years. However, the environmental impacts of the MDC technology have not been studied or well understood. To understand and eventually reduce the environmental impacts of the MDC technology, an attributional life cycle assessment (LCA) model was developed in this study to assess the potential environmental impacts of an MDC from cradle to grave based on a lab-scale prototype system. The results indicate that the MDC manufacturing and operation have relatively large environmental impacts, with manufacturing contributing 22.7% and operation 58.7% of global warming potential in the whole life cycle. The relatively high environmental impacts of the system manufacturing are mainly from the polytetrafluoroethylene (PTFE) binder and the ion-exchange membrane fabrication, while the large environmental impacts during the MDC operation are due to the electricity consumed for water pumping. The electricity generation from the MDC is relatively low at current stage, and it is imperative to further increase the power density to enhance the functionality and improve the environmental performance of the MDC technology. A comparison of MDCs and MFCs with the conventional wastewater treatment method reveals that with further development, this technology may have a promising future in real industrial-scale applications. Highlights: A comprehensive life cycle assessment model of an MDC is developed. The pretreatment, system manufacturing, and operation are the hotspots. The PTFE binder and membranes are main source of impacts in system manufacturing. Increasing power density is crucial to reduce life cycle impacts of MDC technology. The MDCs will outperform conventional wastewater treatment at a high power density.